2020
DOI: 10.1002/jsde.12456
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Dodecenylsuccinic Amide of n‐Phenyl‐p‐Phenylenediammine as Novel Multifunctional Lubricant Additive for Deposit Control and Lubricity

Abstract: A novel multifunctional amide additive N-phenyl-p-phenylenediamine-dodecenylsuccinic anhydride (PPA-DDSA) was synthesized by the reaction of DDSA and N-phenyl-p-phenylenediamine. The successful synthesis of amide additive was confirmed by various analytical techniques like Fourier Transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and thermogravimetric analysis. Performance of prepared additive was evaluated as multifunctional additive for anti-oxidant, detergent dispersant, anti-corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Borated PIBSI is a widely used commercial multifunctional additive to demonstrate dispersancy, anti‐oxidant and anti‐wear activities. Dodecenylsuccinic amide of N‐phenyl‐p‐phenylenediamine also reported in the literature as multifunctional additive as anti‐oxidant, anti‐corrosive, lubricity improver, deposit control additive for engine oil application 15 …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Borated PIBSI is a widely used commercial multifunctional additive to demonstrate dispersancy, anti‐oxidant and anti‐wear activities. Dodecenylsuccinic amide of N‐phenyl‐p‐phenylenediamine also reported in the literature as multifunctional additive as anti‐oxidant, anti‐corrosive, lubricity improver, deposit control additive for engine oil application 15 …”
Section: Introductionmentioning
confidence: 83%
“…Dodecenylsuccinic amide of Nphenyl-p-phenylenediamine also reported in the literature as multifunctional additive as anti-oxidant, anti-corrosive, lubricity improver, deposit control additive for engine oil application. 15 To date, a large number of polymeric additives have been reported which incorporate deposit control characteristics along with low-temperature fluidity and viscosity index improving characteristics to reveal high efficiency during lubricant formulation. A series of long alkyl chain copolymer of (alkyl acrylate-co-maleic anhydride) based novel amides have been reported in a previous research article to demonstrate the viscosity index, pour point, detergent-dispersants, and tribology activities for lubricant applications.…”
Section: Introductionmentioning
confidence: 99%
“…Further, another effort was made to utilize the methyl oleate for developing a novel multifunctional additive in which after thiol‐ene coupling of methyl oleate with thioglycolic acid, esterification was carried with 2,6‐di‐tert‐butyl‐4‐(hydroxymethyl)phenol to introduce the hindered phenolic moiety in the molecular framework. After molecular characterization by spectroscopic techniques like FTIR and NMR, the obtained ester {(S)‐methyl 10‐(2‐(3,5‐di‐tert‐butyl‐4‐hydroxybenzyloxy)‐2‐oxoethylthio)octadecanoate} was analyzed for the estimation of multifunctional properties of additive in polyol lube base oil and also found effective as antioxidant, antiwear, antifriction and anticorrosion additive revealing that the introduced hindered phenolic moiety imparts the multifunctional character in the methyl oleate molecular framework (Faujdar & Singh, 2021; Faujdar et al, 2021). Since alkylated diphenylamines (ADPAs) are also considered to be potent antioxidants and widely used to prevent oxidative degradation of lubricants (Rudnick, 2009; Soleimani et al, 2018), in our study, we have tried to develop a novel methyl oleate‐based amide additive by introducing the diphenylamine moiety in the methyl oleate framework via its thiol‐ene coupling of Tga followed by amide formation with PPA.…”
Section: Introductionmentioning
confidence: 99%
“…González et al [7] issued an amide-type ionic liquid, which can be used as a pure lubricant and a polar oil additive. Faujdar et al [8] found that the amide N-phenyl-p-phenylenediamine-dodecenyl succinic anhydride can be used as a multifunctional and efficient lubricant additive for deposit control and lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 8. The Raman spectra of the worn surface lubricated with different emulsions (velocity 60 mm/s, load 3 N)…”
mentioning
confidence: 99%